2022
DOI: 10.1038/s41467-022-31888-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in Omicron SARS-CoV-2 breakthrough infection in vaccinated adults

Abstract: The SARS-CoV-2 Omicron variant has more than 15 mutations in the receptor binding domain of the Spike protein enabling increased transmissibility and viral escape from antibodies in vaccinated individuals. It is unclear how vaccine immunity protects against Omicron infection. Here we show that vaccinated participants at a super-spreader event have robust recall response of humoral and pre-existing cellular immunity induced by the vaccines, and an emergent de novo T cell response to non-Spike antigens. Individu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 67 publications
7
44
1
Order By: Relevance
“…They also indicate that the higher cross-neutralizing ability of BTI sera is likely due to the superior avidity of antibodies (Fig 4E). This may explain, at least partly, the superiority of hybrid immunity over infection or vaccination alone, and is consistent with ongoing affinity maturation after infection and vaccination(37, 40,41,82,84,86,87).…”
Section: Comparison Of Convalescent Vaccinee and Bti Seramentioning
confidence: 57%
See 3 more Smart Citations
“…They also indicate that the higher cross-neutralizing ability of BTI sera is likely due to the superior avidity of antibodies (Fig 4E). This may explain, at least partly, the superiority of hybrid immunity over infection or vaccination alone, and is consistent with ongoing affinity maturation after infection and vaccination(37, 40,41,82,84,86,87).…”
Section: Comparison Of Convalescent Vaccinee and Bti Seramentioning
confidence: 57%
“…This observation somehow mirrors the restricted cross-neutralizing ability of BA.1-elicited antibodies against pre-Omicron and other Omicron lineages (3, 20, 30, 42, 50, 63, 66, 73, 7577, 89), and highlights that BA.1 is antigenically very distant from all other VOCs and triggers strongly imprinted immune responses. Accordingly one study found that BA.1 booster triggers the activation of naïve B-cells rather than memory B-cells (74), while others record a small proportion of naïve B-cell activation (2, 63, 67, 87). This observation also suggests that different antigens (infection or mRNA vaccines) lead to slightly different immune imprints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such global efforts resulted in the quick approval of effective vaccines [ 3 , 4 , 5 ]. However, the rapid emergence of variants, in particular the Omicron strain (B.1.1.529) subvariants BA.1.1 and BA.2, have resulted in countless breakthrough infections in vaccinated individuals [ 6 ] partially as a result of neutralizing antibody escape [ 7 , 8 , 9 , 10 ], whereas T-cell immunity seemed globally preserved [ 11 ]. Alarmingly, a recent study showed a complete loss of neutralization activity against Omicron variants in vitro for some therapeutic antibodies, thus legitimately raising concerns about their clinical relevance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%